Comparative Evaluation on the Staining Potential of Garcinia mangostana (Mangosteen) and Selenicereus guatemalensis (Dragon Fruit) for Ova of Trichuris suis and Strongyloides ransomi - Doria, Anne Jolina Eustaquio; Dalusong, Crislyn Joy Saballa; Castro, Roma Alheia Mendoza De; Dioneda, Tricia Nicole Malabanan; Estefanio, Kyzha Zen Buencuchillo; Galvez, Liv Andrea Perez; Bremnergo, Pamela Rose F. (Asian Journal of Biological and Life Sciences)
The conventional stains used for the detection of parasitic helminths are hazardous to laboratory scientists, who are exposed to iodine. A potential alternative stain to detect helminth ova is found in this study. This investigates the possibility of a natural dye between Garcinia mangostana (Mangosteen) and Selenicereus guatamalensis (Dragon Fruit) extracts. These fruits contain anthocyanin and betacyanin pigments that stain from purplish to brownish colour. The experiment utilizes distilled water and ethanol with two different concentrations to assess the effectivity of the colour of the pigments in helminth detection. The concentrations tested included 50% ethanol extract of mangosteen, 50% ethanol extract of dragon fruit, 50% distilled water extract of mangosteen, and 50% distilled water extract of dragon fruit. Statistical analysis revealed no significant difference in staining potential between the stain extracts and Lugol’s Iodine. However, further analysis indicated that 50% ethanol extract of mangosteen and 50% ethanol extract of dragon fruit exhibited better staining compared to their distilled water counterparts. The pH values of the stains were also measured, with Lugol’s Iodine having a pH value of 6.0, and the ethanol extracts having a pH value of 5.0, while the distilled water extracts had a pH value of 4.0. Based on the results, it can be concluded that ethanol extracts possess the best staining capacity against distilled water extracts.
Keywords: Anthocyanin; Betacyanin; Garcinia mangostana; Lugol’s Iodine; Selenicereus guatamalensis; Strongyloides stercoralis; Trichuris suis